EXPLOITATION OF GENETIC VARIABILITY FOR QUALITY TRAITS AND AGRONOMIC CHARACTERS IN QUALITY PROTEIN MAIZE (QPM) GERMPLASM (ZEA MAYS L.) - PRAKASH, OM; SHANTI, P.; SATYANARAYANA, E.; SAIKUMAR, R. (Annals of Agricultural Research, 2014)
The present study was undertaken to identify maize lines having high protein, oil and grain yield at two locations during kharif 2001. Per se performance and genetic behaviour for 14 yield and quality parameters were studied in 169 genotypes. The experiment was laid out in simple lattice design (13x13 structure) with two replications. The analysis of variance revealed significant variability for all the agronomic and quality parameters and thus helped in selection of specific parents for different characters. Among the fourteen characters studied, the genetic advance as per cent of mean along with higher values of heritability, GCV and PVC estimates was maximum for grain yield per plot and protein yield, indicating that, the genetic variance for these two traits are probably due to their high additive gene effects. From 169 genotypes evaluated ten best lines were identified for their good agronomic and quality traits and entry numbers 117, 60 and 69 were found to be highest yielders along with good quality characters, suggesting that, these lines could be utilized in future breeding programme in developing high yielding potential QPM hybirds.